2007
DOI: 10.1210/jc.2007-1043
|View full text |Cite
|
Sign up to set email alerts
|

Role of 18F-Fluorodeoxyglucose Positron Emission Tomography in Preoperative Assessment of Cytologically Indeterminate Thyroid Nodules

Abstract: (18)F-FDG PET provides high sensitivity to malignant lesions and may be a potentially useful tool in the evaluation of thyroid nodules with indeterminate cytological findings. For these nodules the number of unnecessary thyroidectomies in a hypothetical algorithm using (18)F-FDG PET would be reduced by 39%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 16 publications
4
41
1
2
Order By: Relevance
“…Occasionally, some of the malignant lesions found in thyroid with the means of PET/CT appear to be metastatic [30]. These data are confirmed in our study population of oncological patients: only one focus of an extrathyroid origin was detected -it was a metastasis of non-small cell lung carcinoma.…”
Section: Allsupporting
confidence: 86%
“…Occasionally, some of the malignant lesions found in thyroid with the means of PET/CT appear to be metastatic [30]. These data are confirmed in our study population of oncological patients: only one focus of an extrathyroid origin was detected -it was a metastasis of non-small cell lung carcinoma.…”
Section: Allsupporting
confidence: 86%
“…Although Sebastianes et al (2007) reported that nodule diameter was not related to SUV, Kim et al (2007) found a significant correlation between SUV and maximum nodule diameter. Sensitivity and specificity were increased for nodules larger than 1 cm (Traugott et al 2010).…”
Section: Incidentalomas Detected By Fdg Petmentioning
confidence: 90%
“…Seven previous studies have evaluated the usefulness of FDG PET for the differentiation of indeterminate nodules of the thyroid, yielding conflicting results (Kresnik et al 2003, de Geus-Oei et al 2006, Kim et al 2007, Sebastianes et al 2007, Hales et al 2008, Traugott et al 2010, Deandreis et al 2012. The sensitivity of FDG PET was 57-100%, depending on the characteristics of the patient population.…”
Section: Incidentalomas Detected By Fdg Petmentioning
confidence: 99%
See 1 more Smart Citation
“…Convectional USG, CT, and magnetic resonance imaging (MRI) have previously been shown to be of some value, but FDG-PET has yet to be assessed in a large prospective study [25]. Table 3 shows a comparison of series examining the utility of FDG-PET in detecting malignancy in a thyroid nodule with indeterminate FNAC findings [25,29,[37][38][39][40][41]. Study size was in the range of 15-51 patients and the criterion for FDG-PET positivity varied among studies.…”
Section: Role Of Fdg-pet In Indeterminate Thyroid Lesions On Fnacmentioning
confidence: 99%